Dopamine and reward hypersensitivity in Parkinson's disease with impulse control disorder - Drew, DS; Muhammed, K; Baig, F; Kelly, M; Saleh, Y; Sarangmat, N; Okai, D; Hu, M; Manohar, S; Husain, M (Oxford University Press, 2020)
Impulse control disorders in Parkinson's disease are common neuropsychiatric complications associated with dopamine replacement therapy. Some patients treated with dopamine agonists develop pathological behaviours, such as gambling, compulsive eating, shopping, or disinhibited sexual behaviours, which can have a severe impact on their lives and that of their families. In this study we investigated whether hypersensitivity to reward might contribute to these pathological behaviours and how this is influenced by dopaminergic medication. We asked participants to shift their gaze to a visual target as quickly as possible, in order to obtain reward. Critically, the reward incentive on offer varied over trials. Motivational effects were indexed by pupillometry and saccadic velocity, and patients were tested ON and OFF dopaminergic medication, allowing us to measure the effect of dopaminergic medication changes on reward sensitivity. Twenty-three Parkinson's disease patients with a history of impulse control disorders were compared to 26 patients without such behaviours, and 31 elderly healthy controls. Intriguingly, behavioural apathy was reported alongside impulsivity in the majority of patients with impulse control disorders. Individuals with impulse control disorders also exhibited heightened sensitivity to exogenous monetary rewards cues both ON and OFF (overnight withdrawal) dopamine medication, as indexed by pupillary dilation in anticipation of reward. Being OFF dopaminergic medication overnight did not modulate pupillary reward sensitivity in impulse control disorder patients, whereas in control patients reward sensitivity was significantly reduced when OFF dopamine. These effects were independent of cognitive impairment or total levodopa equivalent dose. Although dopamine agonist dose did modulate pupillary responses to reward, the pattern of results was replicated even when patients with impulse control disorders on dopamine agonists were excluded from the analysis. The findings suggest that hypersensitivity to rewards might be a contributing factor to the development of impulse control disorders in Parkinson's disease. However, there was no difference in reward sensitivity between patient groups when ON dopamine medication, suggesting that impulse control disorders may not emerge simply because of a direct effect of dopaminergic drug level on reward sensitivity. The pupillary reward sensitivity measure described here provides a means to differentiate, using a physiological measure, Parkinson's disease patients with impulse control disorder from those who do not experience such symptoms. Moreover, follow-up of control patients indicated that increased pupillary modulation by reward can be predictive of the risk of future emergence of impulse control disorders and may thereby provide the potential for early identification of patients who are more likely to develop these symptoms.